2019
DOI: 10.5505/ejm.2019.82713
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Insulin Receptor Substrate 1 (IRS1) Promotes Radioresistance in A172 Glioblastoma Cell Line

Abstract: Insulin receptor substrate 1 (IRS1) is the main adaptor molecule in insulin and insulin like growth factor signaling. Increased level of expression of IRS1 and IGF-1R proteins are associated with many human malignancies. They also induced resistance to therapeutic approaches such as chemo-and radiotherapy in cancer treatment however their molecular mechanisms are still unclear. Glioblastoma Multiforme (GBM) is the most common primary brain tumor in adults and radiotherapy has a pivotal role in its treatment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…MS13 treatment on DU 145 and PC-3 cells also led to the downregulation of several mutually regulated DEGs associated with PI3K pathway, including IRS1, ITGA3, ITGA6, and LAMA3. IRS1 is the principal effector of the insulin and insulin-like growth factor signalling pathways, by which its expression often linked to tumorigenesis and radioresistance (White et al, 1985;Gorgisen et al, 2019). Upregulation of IRS1 increases tumour proliferation and metastasis in many human malignancies, including PCa and breast cancer cells (Chang et al, 2002;Byron et al, 2006;Reiss et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MS13 treatment on DU 145 and PC-3 cells also led to the downregulation of several mutually regulated DEGs associated with PI3K pathway, including IRS1, ITGA3, ITGA6, and LAMA3. IRS1 is the principal effector of the insulin and insulin-like growth factor signalling pathways, by which its expression often linked to tumorigenesis and radioresistance (White et al, 1985;Gorgisen et al, 2019). Upregulation of IRS1 increases tumour proliferation and metastasis in many human malignancies, including PCa and breast cancer cells (Chang et al, 2002;Byron et al, 2006;Reiss et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that mTOR is able to phosphorylate several residues of IRS proteins in the insulin signaling pathway which affect their signaling 40 . IRS-1 has been shown to play a pivotal role in cancer cell proliferation and BRAFi therapy resistance and upregulation is observed in many malignancies 18 , 41 . Here we have shown that concomitant silencing of RPS6 and IRS-1 was able to further potentiate apoptotic cell death in CMM cells and cause a loss in cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%